Whose knowledge? Reflecting on the plurality of knowledge production in contentious politics - Gomes de Matos, Catarina (DIE ERDE – Journal of the Geographical Society of Berlin, 2015)
The links between social protest and scientific research are complex and manifold. This article focuses on some of these connections, adopting a perspective on knowledge in which processes of knowledge production are located in all parts of society rather than being monopolised by academia. Drawing on the empirical example of the Port Vell conflict – a conflict about the the inner-city harbour tramsformation in Barcelona – moments of knowledge production and reproduction are examined. The article shows that social sciences develop and apply general concepts and theories which are adopted by activists. At the same time, protest movements contribute a specific form of alternative knowledge, e.g. about processes of exclusion following current urban transformation while also including situated and embodied consequences of these processes. This perspective on knowledge in various types challenges traditional forms of research. This article forms tentative ideas about alternative roles for researchers.